Shenling Baizhu Powder Alleviates TNBS-Induced Colitis in Rats by Improving Intestinal Epithelial Permeability and Inhibiting Inflammation Through the TLR5/MyD88/NF-κB Pathway - Kehan Rao; Shumin Qin; Shumin Qin; Shumin Qin; Shumin Qin; Shumin Qin; Yuanming Yang; Kai Zhan; Haomeng Wu; Haomeng Wu; Haomeng Wu; Haomeng Wu; et al. (Frontiers Media S.A., 2022)
Aim of the study: To evaluate the protective effect and mechanism of shenling baizhu powder (SBP) on TNBS-induced colitis.Methods: Rats were given TNBS to establish the model of colitis and subsequently treated with different doses of SBP or mesalamine (MES). In addition, the expression of the TLR5/MyD88/NF-κB signaling pathway and critical targets of the intestinal mucosal barrier was detected by immunochemical analysis techniques.Results: SBP significantly ameliorated the symptoms of TNBS-induced colitis in rats and reduced the secretion of pro-inflammatory cytokines. SBP could effectively strengthen epithelial barrier integrity in TNBS-induced colitis by increasing the secretion of mucin and tight junction and inhibiting apoptosis. Furthermore, we identified the crucial role of the TLR5/MyD88/NF-κB signaling pathway in exerting the therapeutic effect of SBP.Conclusion: The results of our study suggest that SBP has therapeutic effects on TNBS-induced colitis and potential value in treating and maintaining remission of colitis.